2004
DOI: 10.1080/01443610410001660724
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective population-based study of primigravid women on the potential effect of threatened miscarriage on obstetric outcome

Abstract: The aim of this study was to ascertain any potential link between threatened miscarriage and obstetric outcome. Threatened miscarriage was associated independently with an increased incidence of abruption (OR 2.8, 2.0-3.7), unexplained antepartum haemorrhage (APH) (OR 2.3, 1.1-5.1) and preterm delivery (OR 2.0, 1.3-3.3). The incidence of low and very low birth weight deliveries, although significantly higher compared with the control population, was not affected independently by this early pregnancy complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 4 publications
8
34
1
3
Order By: Relevance
“…A study done by Mulik et al revealed incidence to be 21.1% which could be due to large sample size taken for the study and use of instrument for the delivery of a distressed fetus. 28 Results from these studies & our study confirm findings from other authors, that threatened abortion is associated with an increased risk of certain pregnancy-related complications, namely abortion, placental abruption, preterm labour, delivery of low birth weight infants and PPROM. 8,30 Generally, high incidence of abortion and adverse pregnancy outcomes in threatened miscarriage indicate the necessity of proper programming in care and also educating high risk women.…”
Section: Instrumental Deliverysupporting
confidence: 91%
See 1 more Smart Citation
“…A study done by Mulik et al revealed incidence to be 21.1% which could be due to large sample size taken for the study and use of instrument for the delivery of a distressed fetus. 28 Results from these studies & our study confirm findings from other authors, that threatened abortion is associated with an increased risk of certain pregnancy-related complications, namely abortion, placental abruption, preterm labour, delivery of low birth weight infants and PPROM. 8,30 Generally, high incidence of abortion and adverse pregnancy outcomes in threatened miscarriage indicate the necessity of proper programming in care and also educating high risk women.…”
Section: Instrumental Deliverysupporting
confidence: 91%
“…30 Mulik et al found a significantly higher risk of placenta praevia at 37 weeks in women who experienced a first-trimester vaginal bleed. 28 …”
Section: Placenta Praeviamentioning
confidence: 99%
“…In sensitivity analysis the exclusion of any one study did not cause the pooled OR to become non-significant, nor increase to more than 2.0. There were no meaningful differences when two studies that only enrolled primigravidas [1213] were excluded (pooled OR=1.77, I 2 =50.3%), as well as after the exclusion of five studies which only included subjects who had achieved at least 28 weeks gestational age[6–9] (pooled OR=1.81, I 2 =53.8%). Of note, 9 studies did not provide a specific lower gestational age cut-off, and cut-offs for the other studies ranged from 20–25.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, collection of outcome data may be subject to inaccuracies with one study relying solely on telephone interviews to obtain final outcomes 13 . A further concern is the lack of clarity regarding the definition of 'threatened miscarriage' and the characterization of symptoms 6 . Few studies quantified symptoms of pelvic pain and vaginal bleeding 10,[13][14][15] , or used validated symptom-scoring questionnaires 10,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%